1997
DOI: 10.1523/jneurosci.17-17-06629.1997
|View full text |Cite
|
Sign up to set email alerts
|

Developing Neonatal Rat Sympathetic and Sensory Neurons Differ in Their Regulation of 5-HT3Receptor Expression

Abstract: Serotonin 5-HT 3 receptors (5-HT 3 Rs) are ligand-gated ion channels expressed by many peripheral neurons and are involved in several physiological processes. To learn more about the developmental regulation of 5-HT 3 R expression, we investigated rat sympathetic and vagal sensory neurons. We found that sympathetic and sensory neurons differ in their regulation of 5-HT 3 R expression during early postnatal life and as these neurons develop in culture. In SCG neurons 5-HT 3 R transcript levels are low at postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Distribution of the 5-HT 3A receptor subunit, as measured by mRNA levels and immuncytochemistry, correlates well with radio-ligand binding studies conducted with high affinity competitive antagonists of the 5-HT 3 receptor (Kilpatrick et al, 1987; Barnes et al, 1989; Laporte et al, 1992; Tecott et al, 1993; Morales et al, 1996; Morales and Bloom, 1997; Rosenberg et al, 1997). Expression of 5-HT 3A receptor mRNA has been measured in the rat forebrain, hippocampus, amygdale, spinal tract of the trigeminal nerve, facial nerve, and the spinal cord dorsal horn (Tecott et al, 1993; Morales and Bloom, 1997).…”
Section: Introduction To the 5-ht3 Receptor A Ligand-gated Ion Chsupporting
confidence: 61%
“…Distribution of the 5-HT 3A receptor subunit, as measured by mRNA levels and immuncytochemistry, correlates well with radio-ligand binding studies conducted with high affinity competitive antagonists of the 5-HT 3 receptor (Kilpatrick et al, 1987; Barnes et al, 1989; Laporte et al, 1992; Tecott et al, 1993; Morales et al, 1996; Morales and Bloom, 1997; Rosenberg et al, 1997). Expression of 5-HT 3A receptor mRNA has been measured in the rat forebrain, hippocampus, amygdale, spinal tract of the trigeminal nerve, facial nerve, and the spinal cord dorsal horn (Tecott et al, 1993; Morales and Bloom, 1997).…”
Section: Introduction To the 5-ht3 Receptor A Ligand-gated Ion Chsupporting
confidence: 61%
“…However, if these same neurons develop in culture without their ganglionic satellite cells and with NGF, they extend dendrites and develop functional cholinergic nicotinic synapses among one another—characteristics more typical of autonomic neurons than of sensory neurons 7,17. We have also shown that neurotrophins affect the expression of 5‐HT 3 R on nodose neurons 18. From these studies, we conclude that the surrounding ganglionic satellite cells exert an important developmental influence(s) on the developing nodose neurons.…”
Section: Differentiation Of Developing Nodose Neuronsmentioning
confidence: 67%
“…7,17 We have also shown that neurotrophins affect the expression of 5-HT 3 R on nodose neurons. 18 From these studies, we conclude that the surrounding ganglionic satellite cells exert an important developmental influence(s) on the developing nodose neurons. Moreover, we find that this influence operates over a brief developmental window, lasting about 2 weeks, before the neurons become fully committed to a sensory phenotype: if neonatal nodose neurons develop with satellite cells for about 2 weeks, either in vivo or in culture, removing the satellite cells and adding NGF has little effect on their subsequent differentiation.…”
Section: Differentiation Of Developing Nodose Neuronsmentioning
confidence: 79%
“…Most of these cortical cells are GABAergic (168,169). Neurons of the peripheral ganglia contain 5-HT 3A subunit receptor mRNA (166,167,170). In contrast, 5-HT 3B receptor subunit transcripts are restricted to peripheral neurons (167) and are not detected in neurons of the central nervous system.…”
Section: -Ht 3 Receptorsmentioning
confidence: 99%